Taxonomical status of Swertia alpestris Baumg. ex Fuss from the territory of Ukraine based on the analysis of the ITS2 secondary structure (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
Based on results of comparative ITS2 secondary structure sequence analysis from the nuclear-encoding ribosomal genes, species status was tested from subalpine population from Ukrainian Carpathian region that were identified using morphological criteria as Swertia alpestris Baumg. ex Fuss. It was found that at the secondary structure ITS2 Swertia alpestris has not differences from species of other populations, that were identified as Swertia perennis L. The taxonomical status of Swertia alpestris are discussed.
Keywords: plant systematics, molecular taxonomy, Swertia alpestris, Swertia perennis, second structure ITS2, Ukraine.